Meteorological Drought Assessment in Koshi and Sudurpaschim Provinces, Nepal - KC, Isha; Adhikari, Brinda; Kayastha, Rijan Bhakta (Journal of Hydrology and Meteorology, 2024)
Drought, characterized by prolonged periods of reduced precipitation and water scarcity, poses significant challenges as a creeping disaster. This study focuses on assessing meteorological drought patterns using the Standard Precipitation Index (SPI) in the Koshi and Sudurpaschim provinces of Nepal from 1980 to 2023. Additionally, it incorporates climate change considerations in drought analysis and utilizes projected precipitation data for the period of 2025-2060 which are bias-corrected ensembles of thirteen GCMs of CMIP6 Project. The findings indicate a consistent trend of dry conditions in the Koshi region since 2005, marked by extreme fluctuations. In contrast, Sudurpaschim has experienced increased precipitation and demonstrated a more stable pattern over the years. Projections suggest heightened drought conditions in both provinces during 2026/2027, 2032/2033, 2045/2046, and 2058, highlighting the need for proactive measures. However, there is a notable trend towards increased precipitation in the far future for both regions. Particularly concerning is the occurrence of winter drought in both provinces across all regions, emphasizing the urgency for targeted strategies to mitigate water scarcity during this critical season.